2021
DOI: 10.1038/s41598-021-85526-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcomes for non-elective neurosurgical procedures in Central Europe during the COVID-19 pandemic

Abstract: The world currently faces the novel severe acute respiratory syndrome coronavirus 2 pandemic. Little is known about the effects of a pandemic on non-elective neurosurgical practices, which have continued under modified conditions to reduce the spread of COVID-19. This knowledge might be critical for the ongoing second coronavirus wave and potential restrictions on health care. We aimed to determine the incidence and 30-day mortality rate of various non-elective neurosurgical procedures during the COVID-19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
2
21
1
Order By: Relevance
“…Interestingly, we could not register any changes in emergency cases, mortality, or night-shift surgery during the pandemic compared to the pre-pandemic time course. Despite this, a decrease in emergency neurosurgical cases, such as traumatic brain injuries, spine conditions, or chronic subdural hematomas, was noticed [18]. However, no decrease in neurosurgical emergencies or night procedures was evident in our study.…”
Section: Emergency Admissioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, we could not register any changes in emergency cases, mortality, or night-shift surgery during the pandemic compared to the pre-pandemic time course. Despite this, a decrease in emergency neurosurgical cases, such as traumatic brain injuries, spine conditions, or chronic subdural hematomas, was noticed [18]. However, no decrease in neurosurgical emergencies or night procedures was evident in our study.…”
Section: Emergency Admissioncontrasting
confidence: 70%
“…Furthermore, SSIs again emerged as the leading cause of readmissions. In the literature, SSIs were found repeatedly to be the most common reason for unplanned readmission [1,6,18]. The majority of unplanned readmissions in neurosurgery belong to the group of preventable readmission categories.…”
Section: Readmissionmentioning
confidence: 99%
“…Our data show a decline in admissions after traffic accidents and performed neurosurgeries, which might be related to each other. An international multicenter study recently showed the same trend for non-elective neurosurgeries in adults in Austria, Switzerland and the Czech Republic, that was partially driven by a decline in traumatic brain injuries (16).…”
Section: Discussionmentioning
confidence: 88%
“…In another study involving 153 emergency general surgery patients during the surge of COVID-19 pandemic, they found a 30-day mortality rate of 7% [26]. Grassner et al [27] examined emergency neurosurgical procedures during the first wave of the pandemic, they found that the 30day mortality did not increase compared to the previous 4 years (between 4,5%-8,9%). They stated that decreased incidence of neurosurgical emergency and this was related to the restrictions placed on mobility within countries [27].…”
Section: Oandsand--#%!3+!t=<! 5!bcd! P(!b?(d! L+-3#%038! 5!bcd! (N!bh'gd! 4and5and-#%!:7-and-8!mentioning
confidence: 99%
“…Grassner et al [27] examined emergency neurosurgical procedures during the first wave of the pandemic, they found that the 30day mortality did not increase compared to the previous 4 years (between 4,5%-8,9%). They stated that decreased incidence of neurosurgical emergency and this was related to the restrictions placed on mobility within countries [27]. In our study, the mortality rates were seen as 8.3% in NS, 6.6% in GS, 3.8% in CVS and 2.7% in orthopedics.…”
Section: Oandsand--#%!3+!t=<! 5!bcd! P(!b?(d! L+-3#%038! 5!bcd! (N!bh'gd! 4and5and-#%!:7-and-8!mentioning
confidence: 99%